Web-Based Strategic Performance Management System for State Universities and Colleges (SUCS) - Raro, Edralin R. (JPAIR Institutional Research, 2018)
Strategic Performance Management System (SPMS) aims to facilitate improvement on how management determines the performance of employees. The system is designed to develop a centralized tool to create, supervise, and monitor the performance of employees and heads of offices who are both teaching and non-teaching staff through the completion of their Office Performance Commitment Review (OPCRs) and Individual Performance Commitment and Review (IPCRs). The system used the Rapid Application Development (RAD) methodology of developing the project. It is a development lifecycle designed to give faster development and higher-quality results than those achieved with the traditional lifecycle. The prototype development process consists of a series of design and builds steps in which the users have the opportunity to fine-tune the requirements and review the resulting software implementation. In addition to the tested software, construction stage deliverables include documentation and instructions necessary to operate the new application, routines, and procedures needed to put the system into operation. The web-based SPMS is user-friendly which means the suggested forms for organizational and individual commitments and performance are similar and easy to complete. The office, division, and individual major final outputs and success indicators are aligned to cascade organizational goals to individual employees and harmonize organizational and staff performance ratings.
Keywords: Information Technology; Performance Monitoring; SPMS; RAD; Philippines